PEMBELAJARAN ONLINE: ANALISIS KESIAPAN BELAJAR DAN MANAJEMEN WAKTU SISWA KELAS VI - Habibah, Putri Junaina Miratul; Thohir, M. Anas (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2022)
This study aims to determine the learning readiness and time management of class VI students in online learning. The study was conducted at MI Raudlatul Mubtadiin Kediri with 18 students as participants consisting of 8 males and 10 females. The data collection technique was carried out by using a questionnaire distributed to all students and interviews with 2 representatives of class VI students. The stages of research are adjusted to case study research. Data analysis techniques using data analysis techniques by Miller include data reduction, data presentation, and concluding. The results showed that students’ readiness for learning in terms of infrastructure was good and there was parental support during online learning. Student time management in online learning has been done through making a daily activity schedule, but it is still in the form of activities that are general in nature but not specific and detailed.